Green Innovation Practices and Its Impacts on Environmental and Organizational Performance - Wang, Haijun; Khan, Muhammad Aamir Shafique; Anwar, Farooq; Shahzad, Fakhar; Adu, Daniel; Murad, Majid (Frontiers in Psychology, 2021)
This study aims to investigate the impact of stakeholders’ views on the practices of green innovation, consequent effect on environmental and organizational performance, and moderating influence of innovation orientation. A quantitative method was employed for the sample size of 515 responses. To accumulate the data from the respondents, convenient random sampling was used. Data were collected from manufacturing and services firms through a field survey by using a closed-ended questionnaire based in the Punjab province of Pakistan. The analysis was done using the structural equation model of the partial least square analysis method. Our findings proved a positive and significant link between stakeholders’ views on green innovation practices. A significant association has been found between green innovation practices and environmental and organizational performance. The moderating effect was found to be negative but statistically significant. This research offers numerous contributions and provides decision-making insinuations.